WDVV equations: symbolic computations of Hamiltonian operators - Vašíček, Jakub; Vitolo, Raffaele (Applicable algebra in engineering, communication and computing, 2022)
We describe software for symbolic computations that we developed in order to find Hamiltonian operators for Witten–Dijkgraaf–Verlinde–Verlinde (WDVV) equations, and verify their compatibility. The computation involves nonlocal (integro-differential) operators, for which specific canonical forms and algorithms have been used.